1993
DOI: 10.1111/j.1346-8138.1993.tb01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Monocyte/Macrophage Markers (CD13, CD14, CD68) on Human Keratinocytes in Healthy and Diseased Skin

Abstract: The results of several investigations proved that, in special circumstances, human keratinocytes (HKs) synthesize and express cell surface moieties characteristic of effector and/or accessory cells of the immune system, such as CD16, CD36, HLA-DR, and intercellular adhesion molecule-1 (CD54), which are all detectable on the surfaces of macrophages. In the present study, skin biopsies from healthy volunteers, from positive tuberculin skin tests, and from patients with acute urticaria (AU), lichen planus (LP), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…, 1997). CD14 expression is also increased in keratinocytes in psoriatic skin, as has been shown using immunohistochemistry, while the keratinocytes of non‐involved psoriatic skin and normal skin are CD14‐negative (Hunyadi et al. , 1993).…”
Section: Introductionmentioning
confidence: 65%
“…, 1997). CD14 expression is also increased in keratinocytes in psoriatic skin, as has been shown using immunohistochemistry, while the keratinocytes of non‐involved psoriatic skin and normal skin are CD14‐negative (Hunyadi et al. , 1993).…”
Section: Introductionmentioning
confidence: 65%
“…In fact, our preliminary analysis showed that APN gene knockdown in dermal fibroblasts abolished many of KCM‐induced gene expression changes in these cells. At the same time, the reciprocal induction of keratinocyte APN expression by fibroblasts illustrates the importance of epidermal–mesenchymal interaction in skin diseases hallmarked by abnormal APN expression in keratinocytes (Hunyadi et al, 1993), and provides supporting evidence for the proposed role of APN in epidermization (keratinocyte growth and differentiation) which is profoundly influenced by the presence of fibroblasts (Robert et al, 1994; Thielitz et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Thus an intricate, cytokine‐based signalling network in the epidermis can form the basis of a cascading inflammatory response in diverse skin diseases. Keratinocytes also possess the ability to synthesize and express cell surface moieties characteristic of effector or accessory cells of the immune system, 67 and there is increasing evidence of the ability of sugars to influence cell‐to‐cell communication among keratinocytes and immune system activity.…”
Section: Immunomodulatory Properties Of Monosaccharidesmentioning
confidence: 99%